HUBUNGAN WAKTU TUNGGU RAWAT INAP DARI UNIT GAWAT DARURAT DENGAN TINGKAT KEPUASAN PASIEN RUMAH SAKIT AWAL BROS BATAM TAHUN 2019 - Yulianti Wulandari; Rizki Sari Utami; Prasetyo (LPPM Universitas Awal Bros, 2020)
Emergency Unit is a service unit in the Hospital that must provide fast and appropriate services so that the objectives of emergency services are achieved and at the same time provide satisfaction to patients. Waiting time is a problem that is still commonly found in the practice of health services. Waiting time is one aspect of the service quality dimension, if waiting time is well managed, the result is customer satisfaction is obtained. At Awal Bros Batam Hospital, waiting time becomes an important priority element because patients can feel dissatisfied with the service due to waiting too long. The purpose of this study was to determine the relationship between waiting time and inpatient satisfaction from the Emergency Room at Awal Bros Batam Hospital in 2019. This type of research uses correlational research with a cross sectional approach. The sample of this study was inpatients from the Emergency Unit obtained by purposive sampling method as many as 186 people. Data is collected by using electronic medical records for waiting time while to find out patient satisfaction is obtained by giving a questionnaire. Data analysis using statistical test Pearson product moment correlation. The results showed that most of the respondents were 165 people (88.7%), while for the satisfaction of the patients most were very satisfied with the service as many as 140 people (75.3%), and there was a sufficient relationship between waiting time and inpatient satisfaction from the Emergency Unit of the Awal Bros Batam Hospital in 2019 (p 0,000 <0,05). Patients with the right waiting time have a greater level of satisfaction. It is hoped that further research will deepen the aspects that affect waiting time and patient satisfaction and solutions to overcome this.